Are larger and/or more symmetrical Drosophila melanogaster (Diptera, Drosophilidae) males more successful in matings in nature? - Sofija Pavković-Lučić; Vladimir Kekić (Revista Brasileira de Entomologia, 2011)
Are larger and/or more symmetrical Drosophila melanogaster (Diptera, Drosophilidae) males more successful in matings in nature? Sexual selection in Drosophila melanogaster, related to body size and fluctuating asymmetry in wing length and number of sex comb teeth in males, was tested in natural conditions. Males collected in copula were significantly larger than those collected as a single, while no difference in mean number of sex comb teeth between copulating and single males was observed. On the other hand, single males had greater asymmetry both for wing length and number of sex comb teeth than their mating counterparts. It looks like that symmetry of these bilateral traits also may play a role in sexual selection in this dipteran species in nature. São maiores e/ou mais simétricos os machos de Drosophila melanogaster (Diptera, Drosophilidae) com mais sucesso nos acasalamentos na natureza? A seleção sexual em Drosophila melanogaster foi testada em condições naturais. Os machos coletados em cópula foram significativamente maiores do que na amostra controle, enquanto que diferenças no número médio de dentes do pente sexual não foram estatisticamente significativas. Por outro lado, os machos que não estavam copulando no momento da coleta foram mais assimétricos, tanto em relação ao comprimento das asas como em relação ao número de dentes do pente sexual. Parece que a simetria dos traços bilaterais pode ter um papel na seleção sexual desta espécie na natureza.